Metode Pendidikan Ahlak Anak Usia Dini dan Relevansinya Terhadap Pendidikan Nasional: (Telaah Pemikiran Al-Ghazali dan Abdullah Nashih Ulwan) - ahmadsanusi sanusi (Universitas Islam Negeri (UIN) Mataram, 2020)
This research is a research-based on library research (Library Research). The progress and sophistication of the times and technology have resulted in many children falling into the abyss of error resulting in moral decadence such as brawls between students, promiscuity, consuming drugs, free sex, and so on. Based on this problem, it is certainly a responsibility for all elements, especially parents and educators to provide the right solution for the next generation of this nation. On that basis, the focus and purpose of this study are to explain the method of moral education according to Imam Al-Ghazali and Abdullah Nashih Ulwan. The relevance of moral education between the two figures' thoughts and the national education system is clearly seen in the definition of education itself, the aims of education, and the educational methods used.